2023
DOI: 10.1055/a-2006-9248
|View full text |Cite
|
Sign up to set email alerts
|

Definition, Häufigkeit und Ursachen der Dystokie beim Pferd – eine Literaturübersicht

Abstract: ZusammenfassungDie Geburt beim Pferd wird dann als Dystokie bezeichnet, wenn eine Gefahr der Schädigung von Stute oder Fohlen durch den Geburtsvorgang ausgeht oder die Notwendigkeit der menschlichen Hilfe zur Beendigung der Geburt vorliegt oder zeitliche Abweichungen in der physiologischen Dauer der Öffnungs- und/oder Austreibungsphase auftreten. Dabei besitzt die Dauer der Austreibungsphase zur Erkennung der Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…A literature review revealed dystocia in mixed mare populations, with rates of 10.1% (McCue & Ferris, 2012) and 11.2% (Ginther & Williams, 1996) Surveys conducted at stud farms indicated dystocia rates ranging from 2% to 13% across these breeds (Ellerbrock & Wehrend, 2023a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A literature review revealed dystocia in mixed mare populations, with rates of 10.1% (McCue & Ferris, 2012) and 11.2% (Ginther & Williams, 1996) Surveys conducted at stud farms indicated dystocia rates ranging from 2% to 13% across these breeds (Ellerbrock & Wehrend, 2023a).…”
Section: Discussionmentioning
confidence: 99%
“…This does not apply to the cases of the present study as obstetric assistance was provided on‐site by a specialized veterinarian. Regardless of the type of treatment, prolonged dystocias are also associated with an unfavourable prognosis for the mare's survival (Ellerbrock & Wehrend, 2023b). In Freeman et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations